UPAYA PELESTARIAN TARI TRADISIONAL BANGSA INDONESIA DARI SEGI HUKUM YANG BERSUMBER DARI HUKUM INTERNSIONAL - I Putu Rio Wijaya; Ni Putu Rai Yuliartini; Muhamad Jodi Setianto (Jurnal Komunikasi Hukum, 2022)
The purpose of this article is to (1) inform the extent of legal protection efforts in preserving traditional dances, (2) and solutions that will be carried out in resolving international conflicts that occur due to cases of copyright claims for traditional dances which are the original cultural heritage of Indonesia by other countries. In making this article the type of research used is normative legal research. The approaches used in assisting the writing of this article are (1) the case approach (2) the analytical approach (3) the statute approach (4) and the conceptual approach. As well as in making this article using primary, secondary, and tertiary legal source materials. The results that can be concluded from the making of this article are (1) the National Regulation on the copyright of a dance is contained in Article 38 of Law no. 28 of 2014. In addition, from an international perspective, soft law is a form of law that has the power to bind it voluntarily, for example, the Universal Declaration of Human Rights (UDHR) 1948 and the International Covenant on Economic, Social and Cultural Rights (ICESCR) 1966 and United Nations Declaration on the Rights of Indigenous Peoples 2007. And Hard Law which has similarities with soft law with both having binding power and also having legal sanctions if violated, for example Convention for the safeguarding of the intangible cultural heritage 2003. (2) Efforts to resolve conflicts legally can be resolved by litigation or non-litigation with the following explanation: Litigation is a form of solving problems involving the law through a court process, both in the form of criminal and civil cases. Which can be achieved by a juridical path, ” The method uses the Pacific Settlement of Disputes, with this method providing accountability for each country in tackling the emergence of disputes, which can disrupt peace and regional harmony, and Non-Litigation is a process of resolving legal problems outside the court, which generally refers to civil cases only. because it tends to be closed. The settlement can be done by: Mediation, and Negotiation.